Identification of Morphology and Morphometry of Fresh Water Fish Cultivated in Meurandeh Teungoh Village, Langsa City - M. Ali Akbar; Khairunnisa; Arini Shinta Zahara; Mardiah; Muliani Tiana Sari; Nurul Adha; Setyoko (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Aquaculture is a fishery activity that produces fish with human intervention to gain profit. Freshwater fish is one of the fishery cultivation commodities that have economic value. Langsa City is one of the cities that has developed freshwater aquaculture. The village in Langsa city that has tried to cultivate freshwater fish is the village of Meurandeh Teungoh. This activity aims to identify the morphology and morphometry of freshwater fish species located in Meurandeh Teungoh Village, Langsa Lama District, Langsa City, Langsa District, Aceh. The methods used in this research are quantitative. Based on the research results, it was found that there were 8 types of freshwater fish consisting of the claridae, pangasidae, anabantidae, cyprinidae, and cichlidae tribes.